2021
DOI: 10.1039/d0cy02230f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of amides to carboxylic acids catalyzed by Nb2O5

Abstract: An efficient heterogeneous Nb2O5 catalytic system has been developed for industrially important and challenging amide hydrolysis reaction to carboxylic acid through cleavage of resonance stabilized amidic C–N bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…The first three oxides were reported to achieve conversion of acetamide to acetic acid over 45%, including 100% conversion over Nb 2 O 5 . The authors proposed mechanisms for the hydrolysis and alcoholysis of amides based on the concerted actions of Lewis-acidic metal cation and basic O anion that attack the carbonyl O and carbonyl C, respectively, and supported them with density functional theory (DFT) calculations on CeO 2 (111). , They also identified a correlation between the increasing basicity of lattice oxygen in metal oxides, as represented by the O 1s binding energy, and higher initial reaction rates for several oxides. It remains unclear why CeO 2 is more effective than Nb 2 O 5 in alcoholysis but not in hydrolysis …”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The first three oxides were reported to achieve conversion of acetamide to acetic acid over 45%, including 100% conversion over Nb 2 O 5 . The authors proposed mechanisms for the hydrolysis and alcoholysis of amides based on the concerted actions of Lewis-acidic metal cation and basic O anion that attack the carbonyl O and carbonyl C, respectively, and supported them with density functional theory (DFT) calculations on CeO 2 (111). , They also identified a correlation between the increasing basicity of lattice oxygen in metal oxides, as represented by the O 1s binding energy, and higher initial reaction rates for several oxides. It remains unclear why CeO 2 is more effective than Nb 2 O 5 in alcoholysis but not in hydrolysis …”
Section: Introductionmentioning
confidence: 81%
“…This has led to investigation into solid ceria (CeO 2 ) as a possible deamidation catalyst. Over the past decade, Shimizu and co-workers demonstrated efficient alcoholysis and subsequent esterification of amides over high loadings of CeO 2 in batch mode in hot, boiling alcohols. Recently, the same group investigated the hydrolysis of acetamide under similar conditions of boiling solvents and high catalyst loadings using various solid oxides including Nb 2 O 5 , ZrO 2 , CeO 2 , TiO 2 , SiO 2 , and Al 2 O 3 , among others as catalysts . The first three oxides were reported to achieve conversion of acetamide to acetic acid over 45%, including 100% conversion over Nb 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the fraction of strong acid sites in all Nb 2 O 5 -T samples, except for Nb 2 O 5 -400, increases Previous studies have demonstrated that niobium oxide exhibits excellent catalytic properties even in the presence of water and/or organic amines. 42,43 Water-blocked niobium oxide could still function as an effective L acid. 44 Besides, kinetic studies suggested that L-acidic Nb 5+ sites interact preferentially with carboxylic acid derivatives in the presence of excess basic molecules, such as water and organic amines.…”
Section: Characterization Of Nb 2 O 5 -Tmentioning
confidence: 99%
“…In a preliminary screening, ANO was applied in the hydrolysis of acetamide under reflux in moderate yield (45%) after 20 h. However, the best results of the study were obtained using the heterogeneous catalyst niobium oxide. 9 (F) Enantiomerically enriched alcohols have an important role in the synthesis of different chiral biologically active compounds present in pharmaceuticals and food products. Enzymatic kinetic resolution (KR) is the most used method to obtain chiral secondary alcohols using lipases as biocatalysts.…”
Section: Spotlight Synopenmentioning
confidence: 99%